Impact of Brand Image and Quality of Service on Satisfaction and Loyalty of Tourists Visiting Atlas Beach Fest Bali - Ni Putu Yumita Arie Puteri; Ni Ketut Arismayanti; I Gusti Putu Bagus Sasrawan Mananda (Cita Konsultindo Research Center, 2024)
Atlas Beach Fest is a popular tourist destination located on the beach in the Canggu tourism area. Atlas Beach Fest is one of the world's largest tourist destinations, offering a combination of relaxation, entertainment, and cultural exploration. Due to changes in tourist behavior when traveling, it is important to carry out research on visitor behavior analysis. Therefore, this research aims to examine the influence of brand image and service quality on the satisfaction and loyalty of tourists visiting Atlas Beach Fest. This research method uses a quantitative approach with a sample of 204 respondents. This research employs accidental sampling as its sampling technique, and collects data through the distribution of questionnaires, interviews, observation, and a literature review. The data analysis technique uses structural equation modeling (SEM) with SmartPLS 3.3.3. The results of this study indicate that: (1) brand image has a positive and significant effect on tourist satisfaction; (2) service quality has a positive and significant effect on tourist satisfaction; (3) tourist satisfaction has a positive and significant effect on tourist loyalty; (4) brand image has a positive and significant effect on tourist loyalty; (5) service quality has a positive and significant effect on tourist loyalty; (6) brand image has a positive and significant effect on tourist loyalty mediated by tourist satisfaction; and (7) tourist satisfaction has a positive and significant effect on tourist loyalty mediated by tourist satisfaction.